2010
DOI: 10.1111/j.1745-459x.2010.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

The Single Interval Adjustment Matrix (Siam) Yes-No Task Applied to the Measurement of Sucrose Thresholds

Abstract: A technique previously unreported in the food sciences literature, the Single-Interval Adjustment Matrix (SIAM) Yes-No task, works by controlling the taster's response criterion, with the goal of producing a bias-free estimate of the absolute threshold. Absolute thresholds were estimated for sucrose in aqueous solution using the SIAM Yes-No task. Obtained estimates were similar to those reported in the literature. These estimated threshold concentrations were then used with the same tasters in a two-alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 24 publications
3
20
1
Order By: Relevance
“…On average, twice as many turnarounds were obtained using the SIAM YN than using the 2AFC task, and with more turnarounds resulting in less measurement error, this is a positive finding for the SIAM YN task. Hautus et al (2010), also measuring sucrose thresholds with the SIAM YN task, reported an average of 8.5 turnarounds for 30 trials across three blocks and 15 participants, and our finding of an average of 19.4 turnarounds across 60 trials is comparable.…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…On average, twice as many turnarounds were obtained using the SIAM YN than using the 2AFC task, and with more turnarounds resulting in less measurement error, this is a positive finding for the SIAM YN task. Hautus et al (2010), also measuring sucrose thresholds with the SIAM YN task, reported an average of 8.5 turnarounds for 30 trials across three blocks and 15 participants, and our finding of an average of 19.4 turnarounds across 60 trials is comparable.…”
Section: Methodssupporting
confidence: 67%
“…Kunka, Doty, and Settle (1981), using a two-down one-up 2AFC adaptive procedure, reported mean sucrose thresholds of −2.8 log M, while Shepherd, Quek and Pathirana (2008) reported thresholds estimated in professionally designed sensory booths (−2.8 log M) and standard laboratory tables (−2.39 log M). Fukunaga, Uematsu, and Sugimoto (2005), using Asian tasters, obtained a mean threshold of −1.77 log M. Hautus et al (2010), in an unrelated experiment, reported sucrose thresholds of −2.16 log M for the SIAM YN task, this being the first demonstration of the SIAM procedure in the gustatory modality. Thus, the SIAM YN data we report here demonstrate convergent validity with preexisting threshold measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While SIAM thresholds obtained from sessions of 60 trials were comparable to those from a 2-IFC task (Shepherd et al, 2011), significant differences were observed between SIAM and 2-IFC in sessions with only 30 SIAM trials (Hautus et al, 2010). In the latter case, some participants showed large variability across sessions.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, a new method called single interval adjustment matrix (SIAM) yes–no task, was used in order to measure sucrose thresholds, with good results (Hautus et al . ). Indeed, in our study, a modified version of the difference from the reference method was used and it was suitable to determine DT and RT of MNEI.…”
Section: Discussionmentioning
confidence: 97%